Estimates of Within-Subject Biological Variation of Protein C, Antithrombin, Protein S Free, Protein S Activity, and Activated Protein C Resistance in Pregnant Women - Kristoffersen, Ann H; Petersen, Per H; Røraas, Thomas; Sandberg, Sverre (Clinical chemistry (Baltimore, Md.), 2017)
In pregnancy, interpretation of results from coagulation parameters can be difficult because of the procoagulant physiological changes. The aim of this study was to describe the course of 5 coagulation parameters (thrombophilia markers) in healthy pregnancies, and to estimate and compare the within-subject biological variation (CV ) of these parameters in healthy pregnant and nonpregnant women. Blood samples were obtained every 4th week during pregnancy and 3 samples after delivery in 20 healthy women and every 4th week during 40 weeks in 19 healthy nonpregnant women. Protein C (PC), antithrombin (AT), protein S free (PS free), protein S activity (PS activity), and activated protein C resistance (with factor V-depleted plasma) (APCR) were analyzed. Before the calculation of CV , results were transformed into multiples of the median (MoM) and natural logarithm of MoM (lnMoM) to adjust for the physiological changes during pregnancy. During pregnancy, PC results showed large variability, AT decreased slightly, and PS free and PS activity decreased significantly. Both activated partial thromboplastin time tests used to calculate APCR decreased, and the APCR ratio was constant. The CV (lnMoM) in pregnancy were for PC 8.4%, for AT 3.8%, for PS free 11.5%, for PS activity 9.3%, and for APCR 0.5%, and similar to corresponding results in nonpregnant women. Transformation of coagulation parameters in healthy pregnancies to lnMoM is a tool to establish a kind of steady state. Although there is a physiological change in PC, AT, and PS free and PS activity during pregnancy, the CV was comparable with the CV of nonpregnant women.